2022
DOI: 10.1177/00219983221137644
|View full text |Cite
|
Sign up to set email alerts
|

Deep reinforcement learning achieves multifunctional morphing airfoil control

Abstract: Smooth camber morphing aircraft offer increased control authority and improved aerodynamic efficiency. Smart material actuators have become a popular driving force for shape changes, capable of adhering to weight and size constraints and allowing for simplicity in mechanical design. As a step towards creating uncrewed aerial vehicles (UAVs) capable of autonomously responding to flow conditions, this work examines a multifunctional morphing airfoil’s ability to follow commands in various flows. We integrated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…3e ). We found that the controller speed was not significantly affected by the pressure tap configurations ( P > 0.05) for all flight conditions and was consistent with rise times established in previous work where DRL controllers showed to be faster than traditional feedback control methods for an MFC morphing wing 42 (Fig. 3f–h ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…3e ). We found that the controller speed was not significantly affected by the pressure tap configurations ( P > 0.05) for all flight conditions and was consistent with rise times established in previous work where DRL controllers showed to be faster than traditional feedback control methods for an MFC morphing wing 42 (Fig. 3f–h ).…”
Section: Resultssupporting
confidence: 90%
“…The two subsequent hidden layers were structured linearly with 512 nodes each and rectified linear unit (ReLU) activation functions 60 , 61 . Due to challenges and time constraints associated with DRL training in hardware environments, many hyperparameters were selected based on previous work performed in a similar MFC morphing environment 42 (Supplementary Table 2 ). However, we tuned the learning rate manually, determining a value of 3 × 10 −5 to be suitable for Adam optimization 62 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maneuverability depends on the ability to quickly change velocity (both speed and direction). Other often neglected aspects of agility and maneuverability in translating avian inspired ideas to UAVs is the speed of actuation and the computing time required to quickly respond 5,6 .…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…MFCs contain piezoceramic fibers embedded in epoxy matrix, which are sandwiched between two polyimide films with interdigitated electrodes, and primarily strains in the fiber direction under voltage input. Due to their flexibility and thinness, MFCs are popular actuators for inducing shape change in morphing aircraft structures, [23][24][25] but they are seldom implemented in deployable space structures. To the authors' knowledge, the only notable examples are in the post-deployed shape correction of composite hinges 26 and reflectors, 27 but initiating deployment with piezoelectric actuation has not been explored.…”
Section: Introductionmentioning
confidence: 99%